IPX066: a novel carbidopa–levodopa extended-release formulation. (February 2012) - Hauser, Robert A
Levodopa (LD) remains the most effective medication to treat Parkinson''s disease (PD). However, most patients develop motor fluctuations and dyskinesias with long-term LD use. It is thought that these response complications are due, at least in part, to LD''s short half-life. Thus, there is great interest in long-acting LD preparations that might be able to provide robust antiparkinsonian benefit through the day and potentially avoid the development of motor fluctuations and dyskinesias. IPX066 is an investigational extended-release carbidopa–levodopa (CD–LD) formulation. It is designed to achieve rapid absorption and onset of clinical benefit, similar to CD–LD immediate release, and to provide more sustained therapeutic LD levels and longer duration of clinical benefit. In Phase III clinical trials, IPX066 was demonstrated to be efficacious in early PD compared with placebo, and in moderate-to-advanced PD, it provided more sustained clinical benefit with fewer dose administrations than CD–LD immediate release, as reported in published abstracts.